Cisplatin, fluorouracil in bolus injection, and leucovorin in first-line therapy for advanced gastric cancer as an alternative to protocols with infusional fluorouracil - Coelho, Rafael Correa (2019)
PURPOSE Gastric cancer (GC) is the fourth most common cancer and the second leading cause of cancer death worldwide. Platinum agents and fluoropyrimidines are the main compounds used in the first-line setting for advanced GC. Given the activity of fluorouracil (FU) bolus, the PFL protocol, a chemotherapy regimen combining cisplatin, FU bolus, and leucovorin, was incorporated at the Brazilian National Cancer Institute, because this schedule does not require hospitalization or infusion pumps. This study aims to evaluate the outcomes of PFL in the first-line setting for patients with advanced GC. MATERIALS AND METHODS This was a retrospective cohort study evaluating patients with advanced GC treated in the first-line setting with cisplatin 80 mg/m2 on day 1 and FU bolus 400 mg/m2 plus leucovorin 20 mg/m2 on days 1, 8, 15, and 22 every 4 weeks, from January 2008 to December 2014. RESULTS A total of 109 patients were enrolled. The median number of cycles received per patient was four (one to 11). Complete responses were achieved in 6.4% and partial responses in 14.7%. Median progression-free survival was 6.3 months (95% CI, 5.08 to 7.58 months) and median overall survival was 8.3 months (95% CI, 6. 79 to 9.87 months). Thirty-four (31.2%) patients were alive in 1 year. Grade 3 and 4 adverse events were experienced by 26.6% and 3.7% of patients, respectively, with dose reduction necessary in 9.1%. CONCLUSION PFL is active in advanced GC and could be an alternative for FU continuous infusion protocols in institutions with limited resources and/or low budget, which is the reality in many nations all over the world.